Two-Hit in vitro T-Cell Stimulation Detects Mycobacterium tuberculosis Infection in QuantiFERON Negative Tuberculosis Patients and Healthy Contacts From Ghana - Adankwah, Ernest; Lundtoft, Christian; Güler, Alptekin; Franken, Kees L. M. C.; Ottenhoff, Tom H. M.; Mayatepek, Ertan; Owusu-Dabo, Ellis; Phillips, Richard Odame; Nausch, Norman; Jacobsen, Marc (Frontiers in Immunology, 2019)
IFN- release assays (e.g. QuantiFERON (QFT)) are widely used for diagnosis of Mycobacterium tuberculosis (Mtb) infection. T-cell responses against QFT antigens ESAT6 and CFP10 are highly Mtb specific but previous studies indicated suboptimal assay sensitivity. Especially for potentially infected healthy contacts (HCs) of tuberculosis patients, alternative antigen usage and more sensitive tests may contribute to improved detection of latent Mtb infection. In a pilot case-control study of tuberculosis patients (n=22) and HCs (n=20) from Ghana, we performed multifaceted in vitro assays to identify optimal assay conditions. This included a two-hit stimulation assay, which is based on initial and second re-stimulation with the same antigen on d6 and intracellular IFN- analysis, to compare T-cell responses against ESAT6/CFP10 (E6/C10) and selected latency antigens (i.e. Rv2628, Rv1733, Rv2031, Rv3407) of Mtb. Considerable subgroups of tuberculosis patients (64%) and HCs (75%) had negative or indeterminate QFT results accompanied by moderate PHA induced responses and high IFN- background values. Intracellular IFN- analysis of E6/C10 specific CD4+ T-cell subpopulations and evaluation of responder frequencies had only moderate effects on assay sensitivity. However, two-hit in vitro stimulation significantly enhanced E6/C10 specific IFN- positive T-cell proportions especially in QFT non-responders, and in both study groups. Mtb latency antigen-specific T cells against Rv1733 and Rv2628 were especially detected in HCs after two-hit stimulation and T-cell responses against Rv2628 were highly capable to discriminate tuberculosis patients and HCs. Two-hit in vitro stimulation may improve moderate sensitivity of short term IFN- based assays, like QFT, to detect Mtb infection. Latency stage-specific antigens added significantly to detection of Mtb infection in HCs and tuberculosis patients with negative QFT test results.